Diurnal behavior of dairy cows on alfalfa pastures supplemented with corn silage and concentrate - Peres Netto, D.; Ribeiro, A.r.b.; Rodrigues, A.a.; Ferreira, R.p.; Mendonça, F.c.; Freitas, A.r.; Campana, M.; Wechsler, Francisco Stefano (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The diurnal ingestive behavior of dairy cows on alfalfa pastures supplemented with corn silage and concentrate was evaluated. Sixteen Holstein dairy cows in mid-lactation were used in a randomized block design. The treatments were partial replacement of corn silage for limited alfalfa grazing time (LGT) or unlimited grazing time (UGT). Rotational alfalfa grazing was used and the amount of concentrate fed was the same in both treatments. Behavioral activities observed were time spent grazing, rumination and idleness, during four days, from 8:00 AM to 7:00 PM. From 2:00 to 5:00 PM grazing was intermittent and short-lasting on UGT, whereas on LGT grazing activity was longer than UGT in the morning and at the end of the afternoon. Restriction in available grazing time clearly influenced the distribution of time spent with grazing, rumination and idleness throughout the day. However, this effect was not observed in the total time spent in these activities.

Avaliou-se o comportamento ingestivo de vacas leiteiras com acesso restrito ou irrestrito a uma pastagem de alfafa suplementada com silagem de milho e concentrado. Utilizaram-se 16 vacas da raça Holandesa, em estádio médio de lactação, em delineamento em blocos ao acaso. Os tratamentos foram: silagem de milho substituída parcialmente por pastejo restrito ou irrestrito de alfafa. As vacas foram manejadas em sistema de pastejo rotacionado e a quantidade de concentrado foi igual em ambos os tratamentos. As atividades comportamentais observadas foram pastejo, ruminação e ócio, das oito às 19 horas, em quatro ocasiões. No pastejo irrestrito, observou-se que, nos horários entre 14 e 17 horas, o pastejo foi intermitente e de curta duração, enquanto no pastejo restrito a atividade de pastejo foi mais prolongada durante a manhã e no final da tarde. A restrição no tempo disponível para pastejo da alfafa influenciou marcadamente a distribuição, no decorrer do dia, do tempo gasto em pastejo, da ruminação e do ócio. Entretanto, não se observou este efeito no tempo total gasto nestas atividades.
Comportamento diurno de vacas leiteiras em pastagem de alfafa suplementada com silagem de milho e concentrado
Keywords: pastejo irrestrito; pastejo restrito; taxa de bocado; unrestricted grazing; restricted grazing; bite rate